Case Report: severe pulmonary hypertension in a child with micronutrient deficiency - Pache-Wannaz, Laure; Voicu, Cristiana; Boillat, Laurence; Sekarski, Nicole (Frontiers in Pediatrics, 2025)
We describe the rare case of a previously healthy seven year-old boy, with an acute clinical onset of severe pulmonary hypertension. He recovered rapidly after vitamin supplementation. Patient history showed a highly selective food intake in the context of autistic features. Thiamine deficiency seemed to be the predominant causing factor aggravated by moderate iron deficiency and supposed vitamin C deficiency. Dietary impact on pulmonary pressures is still poorly understood, but it seems that micronutrient deficiency could be a rare cause of pulmonary hypertension. Relatively frequent in developing countries and mostly in infants, thiamine deficiency should not be forgotten as a potential etiology in the differential diagnosis when patient dietary history is particular.